Genetic Variation of Adenoviruses Causing Conjunctivitis - Rizka Yunanda (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
Human adenovirus type 8 (HAdV-8) is the most common causative agent of a highly contagious eye disease known as epidemic keratoconjunctivitis (EKC). HAdV-8 strains have been classified into genome types HAdV-8A to 8K and HAdV/D1 to D12 according to restriction endonuclease analysis. This review focuses on the significance of HAdV-8 as an agent of EKC. Molecular analysis of HAdV-8 genome types HAdV-53 and HAdV-54 was performed to reveal potential genetic variation in the hexon and fiber, which might affect the antigenicity and tropism of the virus, respectively. On the basis of the published data, three patterns of HAdV-8 genome type distribution were observed worldwide: (1) genome types restricted to a microenvironment, (2) genome types distributed within a country, and (3) globally dispersed genome types. It showed that the HAdV-8 genome types were nearly identical to each other. HAdV-54 is very close to the HAdV-8P, B and E genomes, exceptin the hexon. In a restriction map, HAdV-8P, B, and E share a very high percentage of restriction sites with each other. Hypervariable regions (HVRs) of the hexon were conserved and were 100% identical among the genome types. The fiber knob of HAdV-8P, A, E, J and HAdV-53 were 100% identical. In phylogeny, HVRs of the hexon and fiber knob ofthe HAdV-8 genome types segregated into monophyletic clusters. Neutralizing antibodies against one genome type will provide protection against other genome types, and the selection of future vaccine strains would be simple due to the stable HVRs. Molecular analysis of whole genomes, particularly of the capsid proteins of the remaining genome types, would be useful to substantiate the observations.